New subclasses of meromorphic functions associated with Hadamard product - Faisal, Muhammad Imran; Darus, Maslina; Kilicman, Adem (American Institute of Physics, 2010)
In this paper, we shall study on some new subclasses of meromorphic functions in the punctured unit disk U = {z:0<|z|<1} associated with Hadamard product by using the function Fα(z) = 1/z+Σ∞n = anzn(α−1/α) introduced earlier by the authors [1]. We obtain some interesting results on inclusion and convolution properties of these subclasses.